Exploring and closing the energy balance of eddy covariance measurements along a land use gradient in the West African Sudanian savanna - Nadolski, Laura; Bliefernicht, Jan; Petrovic, Dragan; Rauch, Manuel; Sy, Souleymane; Guug, Samuel; Steinbrecher, Rainer; Neidl, Frank; Hingerl, Luitpold; Kunstmann, Harald (Frontiers in Water, 2024)
A good understanding of land-atmosphere exchange processes is essential for developing sustainable land management practices in Africa, in order to enhance food security and strengthen the resilience against climate change and extremes in this vulnerable region. In this study, we explore the energy balance closure (EBC) of three eddy covariance (EC) sites implemented along a land use gradient (pristine savanna forest, cropland, and degraded grassland) in the Sudanian savanna of West Africa. Our results show that the EBC strongly varies over the monsoon season and the EC sites. However, the best EBC is observed at the pristine site, which has the most homogenous vegetation. Thus, landscape heterogeneity seems to play an important role in the quality of the EC measurements. Moreover, we develop a novel post-closure method based on a quantile-mapping technique conditioned on monsoonal circulation patterns specifically determined for the West African Monsoon. This method is also compared to two well-established methods, the Bowen-ratio (BR) correction and a pure quantile-mapping using various bias measures. Our results show that the novel post-closure method outperforms the other methods and, therefore, leads to better elimination of the underestimation of the turbulent fluxes at the three savanna sites. In addition, specific characteristics of turbulent fluxes, like their strong diurnal cycle, are well represented by the new correction method.